Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Keunggulan Bersaing pada Kedai Janji Jiwa Sepanjang Sidoarjo - Baiq Rielta Raisya Karinda; Lisa Sulistyawati (Universitas Batanghari, 2022)
This study aims to understand and determine the effect of product quality and service quality on competitive advantage at the Promised Spirit Coffee Shop throughout Sidoarjo. The population used in this study were buyers or consumers of the coffee shop in the promise of soul throughout Sidoarjo with Male/Female criteria. The sample required is 100 respondents. The sampling technique used in this research is non-probability sampling. The type of data used in this study is primary data, namely data collected or obtained directly from the object researcher. The data collection technique used in this study was a questionnaire. The data analysis technique used in this research is multiple linear regression. Thus, the results of this study are that simultaneously and partially product quality and service quality have a significant effect on competitive advantage at the Promise Jiwa coffee shop throughout Sidoarjo.